Determinan Kualitas Laba pada Perusahaan Sektor Pertambangan yang Terdaftar di BEI Tahun 2017-2021 - Anastasya Ayu Swacahayawati; Kartika Hendra Titisari; Riana Rachmawati Dewi (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study analyzes the influence of profitability, liquidity, firm size, profit growth and audit quality on earnings quality. Theresearch population is mining sector companiesn isted on the Indonesia Stock Exchange for 2017-2021. The sampling metode used purposive sampling, in which 19 samples were obtained with five years of observation. The data source used is secondary data in the form of the company's annual financial report. The analytical method used is descriptive statistical analysis and multiple linear regression analysis. The results of this study indicate that profitability and firm size affect earnings quality. While liquidity, profit growth and audit quality do not affect earnings quality. If the level of profitability and firm size increases or decreases, it will have an impact on the quality of the profits generated by the company. Meanwhile, if liquidity, profit growth, and audit quality increase or decrease, it will not have any impact on the quality of the profit generated. Keywords: Earnings Quality, Financial Ratio, Firm Size, Profit Growth, Audit Quality